Highlights of the Third International Conference on Immunotherapy in Pediatric Oncology. (1st August 2013) - Brehm, Claudia; Huenecke, Sabine; Pfirrmann, Verena; Rossig, Claudia; Mackall, Crystal L.; Bollard, Catherine M.; Gottschalk, Stephen; Schlegel, Paul G.; Klingebiel, Thomas; Bader, Peter
Abstract : The third International Conference on Immunotherapy in Pediatric Oncology was held in Frankfurt/Main, Germany, October 1–2, 2012. Major topics of the conference included (i) cellular therapies using antigen-specific and gene-modified T cells for targeting leukemia and pediatric solid tumors; (ii) overcoming hurdles and barriers with regard to immunogenicity, immune escape, and the role of tumor microenvironment; (iii) vaccine strategies and antigen presentation; (iv) haploidentical transplantation and innate immunity; (v) the role of immune cells in allogeneic transplantation; and (vi) current antibody/immunoconjugate approaches for the treatment of pediatric malignancies. During the past decade, major advances have been made in improving the efficacy of these modalities and regulatory hurdles have been taken. Nevertheless, there is still a long way to go to fully exploit the potential of immunotherapeutic strategies to improve the cure of children and adolescents with malignancies. This and future meetings will support new collaborations and insights for further translational and clinical immunotherapy studies.